2013
DOI: 10.1186/1472-6963-13-s2-s5
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive and integrated district health systems strengthening: the Rwanda Population Health Implementation and Training (PHIT) Partnership

Abstract: BackgroundNationally, health in Rwanda has been improving since 2000, with considerable improvement since 2005. Despite improvements, rural areas continue to lag behind urban sectors with regard to key health outcomes. Partners In Health (PIH) has been supporting the Rwanda Ministry of Health (MOH) in two rural districts in Rwanda since 2005. Since 2009, the MOH and PIH have spearheaded a health systems strengthening (HSS) intervention in these districts as part of the Rwanda Population Health Implementation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 14 publications
(15 reference statements)
1
67
0
Order By: Relevance
“…Brinkerhoff et al 23 indicated that responsiveness, leadership, customer voice, accountability, transparency, evidence-based practice, efficiency and effectiveness as governing outcome indicators in district health systems. Also, in some other countries, the World Health Organization's (WHO) building blocks were used to assess district health management and related interventions 24 . Whereas, it should be kept in mind that these frameworks weren't developed as specific tools to assess managerial performance at district levels.…”
Section: Discussionmentioning
confidence: 99%
“…Brinkerhoff et al 23 indicated that responsiveness, leadership, customer voice, accountability, transparency, evidence-based practice, efficiency and effectiveness as governing outcome indicators in district health systems. Also, in some other countries, the World Health Organization's (WHO) building blocks were used to assess district health management and related interventions 24 . Whereas, it should be kept in mind that these frameworks weren't developed as specific tools to assess managerial performance at district levels.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, by examining the cycle of service delivery, research and documentation, and policy and program adjustments that feed back into care delivery, overall implementation and evaluation practices can be improved. A few examples from sub-Saharan Africa (and specifically Rwanda, where we work) of this cycle of implementation science, policy uptake, and quality improvement are provided for further reading [3035]. Like the global burden of disease and our collective commitment to lightening the load on those who bear its heaviest weight, global health pedagogy must be dynamic and versatile, with a focus on systemic solutions to address health disparities wherever they occur.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 10 years, Partners In Health (PIH) and its Rwandan counterpart, Inshuti Mu Buzima (IMB), have worked in partnership with the Ministry of Health to bring health care to Kirehe, one of the poorest, rural districts in Rwanda (17). In 2013, PIH and Kirehe district leadership introduced ‘Race to the Top’ ( Inkera y'Imihigo ), a district-wide PBF scheme to reward health centers upon reaching district-identified targets that reflect district-level health priorities, supported with technical support in quality improvement (QI) and peer-to-peer learning.…”
Section: Introductionmentioning
confidence: 99%